Uji Organoleptik Keripik Udang (L. vannamei) Hasil Penggorengan Vakum - Hari Ismanto (Bidang Penyelenggaraan, Kelembagaan dan Ketenagaan Pelatihan - Pusat Pelatihan Pertanian - Badan Penyuluhan dan Pengembangan Sumber Daya Manusia Pertanian - Kementerian Pertanian, 2022)
Organoleptic tests are very important to use in assessing the quality and safety of a food and beverage product. The human senses are the instruments used in organoleptic tests, which include sight, smell, taste, touch and hearing. The vacuum fryer is a technological innovation that can fry fruits, vegetables and fishery products at low temperature and pressure conditions. The advantages of this process include that the product does not burn, the nutrients are not lost, the taste and aroma match the original ingredients and there is no need to use other preservatives. The aim of this study was to determine the consumer's acceptance and preference response to vacuum-fried shrimp chips. The research was carried out in two stages, the first stage was to determine the acceptability and preference for shrimp chips produced by vacuum frying at three frying temperature treatments (80°C, 85°C, 90°C). The second stage of research was to determine acceptance and preference for shrimp chips resulting from vacuum frying from the recommended frying temperature of the first stage research combined with three freezing temperature treatments (-2°C, -12°C, -24°C). Organoleptic tests were carried out on 60 untrained panelists on shrimp chips based on aroma, taste, texture and color parameters. Organoleptic test results on vacuum fried shrimp chips, the highest score was obtained at 90°C vacuum frying temperature and -2°C freezing treatment. The results of the shrimp chips quality test successively were taste, color, texture and scent.